Social Media and Advertising: An Exploratory Study on the Lifestyle of Generation Y Consumers in Malaysia - Ohajionu, Uchechi Cynthia; Mathews, Soney (2016)
One out of every seven people in the world today has a Facebook page and about four out of every five active internet users visit social networking sites and blogs. There is an increasing adoption of social media advertising by corporations. Social media has become an integral part of the consumers’ daily lives as well as corporate organisations’ day-to-day operations. This growth is an indication of a longterm trend toward social media usage among corporations (as well as individual brands) becoming the norm. This paper explores responses to social media advertising to determine if Generation Y consumers in Malaysia with different demographic characteristics differ in their attitude towards social media advertising, purchase intention and actual purchase of products and services advertised on social media. It also provides useful insight to enable businesses ensure more efficient utilization of their advertising budget and development of more effective advertising strategy.